Athapaskan Matriliny and Trade In Canada and Alaska - Allen, Wallingford Wayne (My University, 1971)
This thesis puts forward an explanation for the presence of matrilineal descent groups among the Athapaskan speaking people of Alaska and the western sub-Arctic of Canada. The hypothesis put forward here is that matrilineal descent groups apread from the Tlingit to the Athapaskan peoples, as a result of the more profitable) their trade with Athapaskans.
Membership in Tlingit descent groups apread to Athapaskans who became trading partners of the Tlingit and who married Tlingit women. This pattern of trading partnerships and intermarriage was copied by the Athapaskan and resulted in the apread of matrilineal descent groups into the interior.
Keywords: Anthropology; Sociology; Anthropology